Historical and Current Geopolitical Positioning of Ukraine: Is It Central or Eastern Europe? (Politeja, 2018)
The academic paper is focused on developing historical and current geopolitical positioning of Ukraine in Europe. The scholars have attempted to solve the problem of affiliation of Ukraine to a specific sub‑region of Europe – Central and/or Eastern. It has been reasoned and argued that on the map of the European sub‑regions, Ukraine occupies an extremely specific and mixed position, as its affiliation to any certain sub‑region has always been historically and geopolitically determined, however it largely correlates with some attributes inherent both to Central and Eastern Europe. In conclusion it has been specified that Ukraine, being a boundary country, is characterized by a paradoxical geopolitical position and inconstant nature of its geopolitical projection within the frames of the sub‑regions in Central and Eastern Europe.